Post-breeding dispersal of frigatebirds increases their exposure to mercury. Issue 1 (15th June 2017) - Mott, Rowan; Herrod, Ashley; Clarke, Rohan H.
Abstract: Migration and dispersal can expose wildlife to threats in different parts of their range, particularly for localized anthropogenic threats. Wildlife exposure to metal contaminants may correlate with local anthropogenic emissions. Feather mercury concentrations of adult and juvenile Lesser Frigatebirds ( Fregata ariel ) and Great Frigatebirds ( F. minor ) were determined for individuals breeding in the eastern Indian Ocean. Low mercury concentration in juveniles relative to adults, higher mercury concentration in adult females than adult males, and a trend for Lesser Frigatebirds to have higher mercury concentration than Great Frigatebirds implicate non-breeding ground exposure as the major influence on mercury burden. Aspects of foraging ecology are congruent with high exposure occurring in inshore waters of the non-breeding range, particularly in the South China Sea. These findings highlight the need for tighter mercury emission regulations in southeast Asia to minimise the potential threat to frigatebirds and other species dependent on marine resources including humans. Graphical abstract: Highlights: Frigatebirds accumulate low mercury burden from prey caught near breeding grounds. High mercury exposure in southeast Asia is inferred from non-breeding ecology. Mercury emission policy and enforcement must improve in southeast Asia.